Content-Based Approach in Developing Listening Comprehension in English Language: Basis for Proposed Listening Activities - Salape, Rodora L.; Maming, Jimmy Bernabe; Maravilla, Wes Harven G. (Future Science / FSH-PH Publications, 2023)
This study was based on the teacher's observations of the students' comprehension of questions, passages, and literary works during the listening session. One of the numerous reasons why listening comprehension is underestimated among the four macro skills is the lack of exposure to real-world content. Numerous listening resources also conflict with the students' real-world circumstances and past knowledge, making it difficult for them to stay involved in the course. This is the justification for the study's execution. In that situation, the researcher searched for strategies and listening practice materials to aid the students in developing their English listening comprehension abilities by turning to the content-based method for support and developed listening exercise materials that would aid in the English language learning of grade 8 children. Pre-experimental design with a single group pretest-posttest was the methodology employed in this study. Based on the pretest they took prior to the treatment, 100 eighth-grade students' listening comprehension abilities were evaluated. After that, a post-test was administered to gauge how well the treatment and content-based approach had worked. The researcher also used the following statistical software or formulas: Probability and percentage distribution, standard deviation, t-test, and weighted mean: Assuming Equal Variances for Two Samples.